Revealing the secret life of pre-implantation embryos by time-lapse monitoring: A review - Azita Faramarzi; Mohammad Ali Khalili; Giulietta Micara; Azam Agha- Rahimi (Shahid Sadoughi University of Medical Sciences, 2017)
High implantation success following in vitro fertilization cycles are achieved via the transfer of embryos with the highest developmental competence. Multiple pregnancies as a result of the transfer of several embryos per cycle accompany with various complication. Thus, single-embryo transfer (SET) is the preferred practice in assisted reproductive technique (ART) treatment. In order to improve the pregnancy rate for SET, embryologists need reliable biomarkers to aid their selection of embryos with the highest developmental potential. Time-lapse technology is a noninvasive alternative conventional microscopic assessment. It provides uninterrupted and continues the survey of embryo development to transfer day. Today, there are four time-lapse systems that are commercially available for ART centers. In world and Iran, the first time lapse babies were born in 2010 and 2015, respectively, conceived by SET. Here, we review the use of time-lapse monitoring in the observation of embryogenesis as well as its role in SET. Although, the findings from our review support common use of time-lapse monitoring in ART centers; but, future large studies assessing this system in well-designed trials are necessary.